2009
DOI: 10.1007/s00404-009-1311-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of genitourinary fistulae: comparison of our experience at Turkey and Niger

Abstract: A high percentage of patients with genital fistulae can be rendered dry and continent by assessment of these conditions; meticulous attention must be applied for the absence of inflammation and infection at the fistula site before the operation. Surgical team must be experienced at both abdominal and vaginal repair. Broad-spectrum antibiotics and continuous bladder drainage must be applied to all patients for at least 2 weeks. Interposition flaps must be used in complex cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Among our examinees, when taking everything into consideration, in 23 patients whose vesicovaginal fistulas were surgically treated with transabdominal, transvesical or transvaginal approach, cumulative successfulness of the VVF repair, when performed for the fourth time, was 100%, with a remark that we lost track of one patient after having an unsuccessful primary repair of VVF. These results are comparable with many other published reports (30,31,32). Sahito et al wrote about the successfulness of the primary surgical repair with the abdominal approach in 30 patients with VVF in 86.67 % of cases (33).…”
Section: Discussionsupporting
confidence: 90%
“…Among our examinees, when taking everything into consideration, in 23 patients whose vesicovaginal fistulas were surgically treated with transabdominal, transvesical or transvaginal approach, cumulative successfulness of the VVF repair, when performed for the fourth time, was 100%, with a remark that we lost track of one patient after having an unsuccessful primary repair of VVF. These results are comparable with many other published reports (30,31,32). Sahito et al wrote about the successfulness of the primary surgical repair with the abdominal approach in 30 patients with VVF in 86.67 % of cases (33).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, ureteral injuries were recognized intraoperatively in 9 patients (33.3%) and postoperatively in 18 patients (66.7%). In the time after surgery, it is necessary to evaluate immediately when suspicious complications presented [9]. When unilateral ureteral obstruction happened in the first 24 to 48 hours after surgery, serum creatinine level may show a transient increase [8].…”
Section: Discussionmentioning
confidence: 99%
“…4,27 The reason for tissue interposition is to promote healing (via improved blood supply and lymphatic drainage) and avoid overlapping suture lines. 1,[28][29][30][31] Those most commonly used during transvaginal repair are paravaginal fascia, peritoneal flaps (for proximal fistulae) and Martius (labial) fat pad flaps (for more distal fistulae). 4,28,29,31 They are well-vascularized tissues, and in a recent single-centre study excellent success rates over 10 years in a cohort of 83 patients were reported with tissue flap interposition regardless of tissue type.…”
Section: Tissue Interpositionmentioning
confidence: 99%
“…28 They are regarded as particularly important protective factors in the transvaginal repair of more complex fistulae. 28,29 Omentum is widely regarded as the interposition flap tissue of choice for transabdominal repair. A recent review by Evans et al found a higher success rate (100% for both benign and malignant aetiology) for transabdominal repairs performed using an omental flap than without (63% for benign aetiology and 67% for malignant aetiology) suggesting that this remains paramount to the success of the procedure.…”
Section: Tissue Interpositionmentioning
confidence: 99%
See 1 more Smart Citation